Effects of different soybean meal processing techniques on growth performance of pigs - Woodworth, J.C.; Musser, R.E.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 35-d growth trial was conducted to determine the influence of different soybean meal processing techniques on starter pig growth performance. From d 0 to 14 after weaning, all pigs were fed a common diet. Then pigs were fed six experimental diets from d 14 to 35 after weaning. Three treatment comparisons were made. Pigs fed a diet containing extruded-expelled soybean meal (SBM) without hulls (Insta-Pro) were compared to those fed solvent-extracted SBM (46.50/0 CP) and 3.21% soy oil. Pigs fed a diet containing extruded-expelled SBM with hulls (lnsta-Pro) were compared to those fed a diet containing 44% CP SBM and 4.57% soy oil. Pigs fed a diet containing a second expelled SBM product with hulls (Soyplus) were compared to those fed a diet containing 44% CP SBM and 1.61% soy oil. Pigs fed either Insta-Pro extruded-expelled diet had similar growth performance to pigs fed diets containing conventionally processed soybean meal and added oil. Pigs fed diets containing Soyplus had numerically lower ADG and higher F/G than pigs fed any other treatment. These data suggest that Insta-Pro extruded-expelled SBM can replace conventionally processed SBM and added soy oil on a lysine and energy basis without affecting growth performance.
Keywords: Swine; Soybean meal; Processing; Growth; Starter pigs